Pengaruh Penerapan Aplikasi Pendaftaran Online Terhadap Pelayanan Pendaftaran Rawat Jalan di Rumah Sakit Hasna Medika Cirebon - Arnita, Hasnah; Yuyun Yunengsih (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The online outpatient registration system is a technological innovation in healthcare aimed at enhancing the efficiency of registration services. One of its implementations is carried out at Hasna Medika Cirebon Hospital through the Mobile JKN application. However, several challenges persist in its execution. This study aims to evaluate the impact, benefits, challenges, and solutions related to the use of the online registration application at Hasna Medika Cirebon Hospital. The research employs a qualitative descriptive method with purposive sampling. Informants include the head of the medical records department, registration staff, customer service officers responsible for managing Mobile JKN, and patients using the application. Data were collected through observation and interviews, followed by analysis through the processes of data collection, reduction, presentation, and conclusion drawing. The findings indicate that the implementation of the online outpatient registration system positively impacts the reduction of the registration staff's workload and facilitates patient access. Nevertheless, challenges remain, particularly for elderly patients without smartphones or those visiting the hospital unaccompanied. The hospital addresses these issues by providing patient education on system usage.